PERUVIAN LEGAL SYSTEM AND SYSTEMIC LAW IN BRAZIL: AN ALTERNATIVE PROPOSAL FOR CONFLICT RESOLUTION - Miñano Donayre, Alicia Liceth (2025)
The present work arises in part, thanks to the studies on Ontological Coaching at the Newfield Network international school (2015), where there is an insight into the subjective part of the human being, as well as an approach to other proposals with this same end, as are the family constellations of Bert Hellinger. This framework has allowed that, in the field of legal scientific research, an inquiry can be made about what is happening in Brazil and other parts of the world, with the so-called Systemic Law, to reflect on whether this could be combined with the Peruvian legal system, taking as a basis the approaches of Edgar Morin through the paradigm of complexity; to finally decant in a brief review of our alternative means of conflict resolution, concluding and proposing the Brazilian systemic model as a possibility for the solution of extrajudicial conflicts in Peru.